New therapeutic options in migraine treatment - Kłos, Aleksandra; Pawlicki, Mateusz; Stachyrak, Karol; Mika, Dawid; Mazur, Bartosz; Turek, Kamila; Lambach, Maciej; Greguła, Anna; Mazurek, Aleksnadra; Wilanowska, Wiktoria (Journal of Education, Health and Sport, 2024)
Introduction and purpose Migraine is a common disease mostly affecting women. It has a huge influence on patients’ life strongly decreasing its quality by cause of repetitive headache episodes and often comes with unpleasant and burdensome symptoms like photophobia, nausea or vomiting. This article focuses on migraine treatment, especially on new drugs. Primary drugs used in migraine attacks are non-steroid anti-inflammatory drugs (NSAI) and triptans. Because of their side effects and impact on internal organs, these substances are often contraindicated or inefficient. The same applies to triptans, which cannot be used by patients with cardiovascular diseases. Due to the need of a new migraine treatment path development, new remedies have been found, bringing hope for patients who could not use prior options. They are divided into two groups: ditans (lasmiditan), which are 5-HT1F serotonin receptor agonists and gepants (ubrogepant, rimegepant, atogepant and zavegepant), which are CGRP receptor antagonists. A summary of the current state of knowledge is intended to increase the awareness of physicians and patients when selecting the appropriate treatment. Material and methods The following review was based on articles obtained from the PubMed and Google Scholar databases. Key search terms included migraine, ditans, gepants, migraine treatment. Conclusions Drugs described in this study clearly show the new pathway of migraine treatment and prevention. They are safer and show more benefits than substances currently used. They can also be used in wider range of patients with conditions marked as contraindications for current schemes. However more research is still needed to fully describe their characteristics.